Analisis Peran Leadership Style Pengusaha Wanita Dalam Meningkatkan Daya Hidup (Viability) Kluster UMKM Di Sumatera Barat - Aimatul Yumna; Selli Nelonda (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2018)
This study aims to know and analyze how the role of leadership style, the influence of internal and external characteristics of female entrepreneurs in improving the endurance of SME clusters in West Sumatra. By using primary data and multiple regression model, there are several classification of business field dominating Micro Small Industry in West Sumatera, namely food industry, textile industry, apparel industry and craft industry and furniture industry. From the results of the study, the ability to survive (viability) of SMEs in West Sumatra is still small and will increase when UMKM participate in training and mentoring and led by women because it is considered more experienced even though low educated. The ability to survive which is represented by net profit margin will be bigger when SMEs expands the market out of province or abroad, while other variables are industry characteristic, entrepreneur characteristic and capital unrelated to the improvement of survival ability of SMEs.